Optimization of drill bit geometries for minimum thermal damage in bone drilling - Mohd Faizal, Ali Akhbar; Mohamad Faris, Mohd Ashri; Ahmad Razlan, Yusoff; Shahrizan, Jamaludin; Rodianah, Alias; Fatin, Alias; Razhan, Hassan; Muhammad, Rizwan (Akademi Baru, 2024)
Thermal injury is a common post-operative effect in bone drilling surgeries. The extreme heat generated during the drilling process kills bone cells, which causes irreversible bone death. This bone death loosens medical fixations—screws, plates, and implants—and subsequently refractures the bone. Research on drill bit geometries in bone drilling has attracted interest from engineering and medical researchers. However, previous research has mainly focused on the simulation of bone drilling, which could generate an incorrect approximation of thermal bone damage if the simulation model is not validated. For this reason, this study focuses on the optimization and parametric analysis of the bone temperature elevations induced by customized drillbitfeatures—point angle (60-180°), web thickness (25-50 %), and helix angle (10-55°)—in comprehensive ex-vivo bone (bovine) experimental drilling tests. The L9Taguchi optimization method was then applied to determine the optimal design to minimize maximum bone temperature rise. Results from the parametric analysis revealed that the optimal setup for the drill point features can be obtained with the ranges of point angle of 160-180°, web thickness of 25-30 %, and helix angle of 30-40°. Based on the Taguchi optimization results, the minimum thermal damage is produced with the point angle of 180°, web thickness of 25 %, and helix angle of 35°. This work offers a promising solution for reducing thermal injury and preventing thermal osteonecrosis in bone drilling surgeries.